2013
DOI: 10.1071/an12292
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the concept, conduct and findings of the producer-led Cicerone Project

Abstract: Abstract. The Cicerone Project began as a producer-led partnership that sought, over a period of 8 years, to enhance the profitability and sustainability of livestock enterprises by improving the connection between those producers, research and extension. Following a detailed survey, the research and extension needs of livestock producers were identified and several applied investigations were conducted to meet those needs and delivered through a range of extension activities. This final paper of the Cicerone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Colletes gigas is one of the main pollinators of C. oleifera. It can easily carry pollen when collecting nectar from C. oleifera, but pollen from C. oleifera is toxic to bee larvae (Xie et al, 2013). The pollen produced by male sterile 'Huashuo' plants is not only small but is also low in vitality.…”
Section: Discussionmentioning
confidence: 99%
“…Colletes gigas is one of the main pollinators of C. oleifera. It can easily carry pollen when collecting nectar from C. oleifera, but pollen from C. oleifera is toxic to bee larvae (Xie et al, 2013). The pollen produced by male sterile 'Huashuo' plants is not only small but is also low in vitality.…”
Section: Discussionmentioning
confidence: 99%
“…Funds were committed for the setup cost of the farmlets and then ongoing costs were needed for the support of administrative and farm staff, as well as for ongoing expenses of soil testing, fertilisers, supplementary feeding and other general running expenses. Details of the overall funding of the Cicerone Project have been described and discussed in a related paper by Coventry et al (2013). Throughout the Project, there was considerable reliance on in-kind contributions from collaborators not only during the planning phase but also during the operational phase and especially during the publication phase.…”
Section: Budget Needsmentioning
confidence: 99%
“…As noted in the final paper of this Special Issue (Coventry et al 2013), the high degree of commitment shown by institutional partners to the Cicerone Project would have been even greater if a mechanism could have been found to provide some funding to support those contributions made by partners. For example, in the final year of the Project, when a decision was taken to conduct a substantial outreach effort to different regions, some marginal funding was provided by the Cicerone Project to assist the extension partner, NSW DPI.…”
Section: Formal Extension Assessmentmentioning
confidence: 99%
“…A complementary paper by Sutherland et al (2013) explains the origin of the Project while another details the surveying of livestock producers (Kaine et al 2013) to learn of their most pressing problems. Many other papers detail the overall methods and results while the final paper provides 'reflections' from the Cicerone Board members on the success or otherwise of the overall Project (Coventry et al 2013).…”
Section: Introductionmentioning
confidence: 99%